ANALISIS FAKTOR RISIKO KEJADIAN DEMAM BERDARAH DENGUE (DBD) DI KELURAHAN PADANGSAMBIAN - Dwiyanti NM (Coping: Community of Publishing in Nursing, 2014)
Padangsambian village is an endemic area of dengue hemmorhagic fever (DHF) in Denpasar in 2012. The incidence is related to the risk factors of DHF. This study aimed to analyze the existence of container, resident mobility, and eradication of mosquitoes breeding places as DHF risk factors and the most dominant factor which influenced DHF cases in Padangsambian village. This was an observational analytic study using case-control design. The sample size is 90 respondents which are divided into two groups, case group and control group, with the same amount of sample for each group. The result of chi square test showed that the existence of container (p=0,000), resident mobility (p=0,003), and eradication of mosquitoes breeding places (p=0,000) were the risk factors of DHF. The multivariate analyze using logistic regression model showed that eradication of mosquitoes breeding places was the most dominant risk factor of DHF in Padangsambian village (OR=23,642; CI=5,340 – 104,676). Therefore, it is suggested to community health nurse in Padangsambian village to increase the health promotion of DHF prevention by doing 3M Plus activities.